2011
DOI: 10.1016/j.meatsci.2011.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of mechanically deboned poultry meat and collagen fibers on quality characteristics of frankfurter-type sausages

Abstract: The effects of mechanically deboned poultry meat (MDPM) and levels of collagen fibers on comminuted, cooked sausage quality characteristics were investigated using the central composite rotatable design of response surface methodology (RSM). Use of collagen fiber as an additive affected the sausage characteristics, but the effect depended on the amount of the MDPM used. While MDPM additions resulted in higher cooking loss and darker and redder frankfurters, the addition of collagen fibers improved cooking yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
86
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 17 publications
21
86
1
14
Order By: Relevance
“…Moreover T1, T2, and T3 had the lowest adhesion values; therefore, inulin (T3) did not affect this parameter. Pereira et al (2011) reported that this feature should be smooth and without adhesion. T1 had the lowest adhesiveness value; this suggests that fat and dietary fibers were responsible for restructuring the sausages.…”
Section: Shear Force (Sf) and Texture Profile Analysis (Tpa)mentioning
confidence: 98%
“…Moreover T1, T2, and T3 had the lowest adhesion values; therefore, inulin (T3) did not affect this parameter. Pereira et al (2011) reported that this feature should be smooth and without adhesion. T1 had the lowest adhesiveness value; this suggests that fat and dietary fibers were responsible for restructuring the sausages.…”
Section: Shear Force (Sf) and Texture Profile Analysis (Tpa)mentioning
confidence: 98%
“…The average of percentage of hydrolysis obtained in 120 minutes of process for each substrate, the standard deviation and the Tukey test (at the 95 % level of confidence) are shown in Table 1. The crude collagen fiber (coarse fraction) and the powdered collagen fiber (fine fraction) are from by-products of tanneries, such as dermis and subcutaneous tissue, that were previously subjected to chemical and heat treatment, but the powdered collagen fiber is subjected to higher temperatures and subsequent grinding (PEREIRA et al, 2011).…”
Section: Degree Of Hydrolysis (Dh) Of the Substratesmentioning
confidence: 99%
“…Os efeitos dos níveis de nitrito de sódio (43,6; 150; 256,4; e 300ppm), das doses de radiação gama (2,9; 10; 17,1; e 20kGy) e possível interação foram avaliados por um Delineamento Composto Central Rotacional (DCCR), em fatorial 2x2, com quatro pontos fatoriais, quatro pontos axiais e três pontos centrais, totalizando 11 ensaios (PEREIRA et al, 2011), realizados em ordem aleatória.…”
Section: Methodsunclassified